Differential effects of heparin and low molecular weight heparin on osteoblastogenesis and adipogenesis in vitro - Osip, Stephanie L.; Butcher, Martin; Young, Edward; Yang, Lufang; Shaughnessy, Stephen G. (Thrombosis and Haemostasis, 2004)
We have previously demonstrated that heparin produces cancellous bone loss in rats due in part to a decrease in the number of osteoblasts lining the trabecular bone surface. In the present study, we use a stromal-derived cell culture system together with measurements of alkaline phosphatase (ALP) activity, to compare the effects of heparin and the low molecular weight heparin (LMWH), Fragmin, on osteoblast differentiation in vitro. In addition, we examined the possibility that both heparin and LMWH can induce adipogenesis in our stromal cell culture system. Both heparin and LMWH were found to produce a statistically significant (P <0.01) and concentration-dependent decrease in the number of osteoblasts while increasing the number of adipocytes. When the effects of gravimetrically equivalent amounts of heparin and LMWH were compared, heparin had a 4-fold greater effect than LMWH. In contrast to heparin, N-desulfated heparin was found to have minimal effects on both osteoblast and adipocyte differentiation indicating that the heparin effect is not only chain-length dependent but also charge-dependent. The observation that LMWH has less of an effect on bone formation than heparin is compatible with the results of clinical trials indicating that LMWH produces less bone loss after long-term administration.
Keywords: Heparin; low molecular weight heparin; bone; osteoblastogenesis; adipogenesis